Contact Tracing of Children Living With Sputum Positive Adult Cases of Pulmonary Tuberculosis, In Urban Ghaziabad: A Hospital Based Cross Sectional Study: Improving Contact Tracing for Pulmonary Tuberculosis in Urban Ghaziabad (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Background Contact investigation of tuberculosis (TB) is active case finding strategy for the diagnosis of tuberculosis in contact and is an important component of detection of TB core part of TB detection program. In high incidence setting like India, the yield of household contact screening and approaches is limited.Objective Household contact screening of newly diagnosed pulmonary TB index cases factors associated with it.Material and Methods Details of index cases were collected from the DOTS centre Ghaziabad. Telephonic calls were conducted to identify newly diagnosed pulmonary index cases of TB with their household contacts. Standardized protocol were used to screen symptoms of active TB in household contacts aged 0-18years with sputum for acid fast bacilli (AFB) examination chest X-ray examination with Mantoux test.Result A total of 778 household contacts of 160 index cases of pulmonary TB were identified, in which 74 (9.5) were symptomatic. Among these, 54 (73.6) were evaluated for sputum examination, resulting in 16(29.1) of sputum smear positive TB with 4 (7.4) were sputum smear negative TB.Conclusion While following standard protocol systematic implementation for conducting household contact investigation, additional TB cases in community can be identified and can provide great support for chasing the dream of “TB free INDIA 2025”.